Ending the message: poly(A) signals then and now. - Proudfoot, N (2011)
Polyadenylation [poly(A)] signals (PAS) are a defining feature of eukaryotic protein-coding genes. The central sequence motif AAUAAA was identified in the mid-1970s and subsequently shown to require flanking, auxiliary elements for both 3'-end cleavage and polyadenylation of premessenger RNA (pre-mRNA) as well as to promote downstream transcriptional termination. More recent genomic analysis has established the generality of the PAS for eukaryotic mRNA. Evidence for the mechanism of mRNA 3'-end formation is outlined, as is the way this RNA processing reaction communicates with RNA polymerase II to terminate transcription. The widespread phenomenon of alternative poly(A) site usage and how this interrelates with pre-mRNA splicing is then reviewed. This shows that gene expression can be drastically affected by how the message is ended. A central theme of this review is that while genomic analysis provides generality for the importance of PAS selection, detailed mechanistic understanding still requires the direct analysis of specific genes by genetic and biochemical approaches.